Aquatic Pathogens are Subjected to Biosynthesis, Purification and Antibacterial Activity - Sinha, Ajay; Chaudhary, D.; Mukherjee, A.V. (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
The size and shape of the nanoparticles can be controlled by varying the ratio of metal salts to apiin compound in the reaction medium. The resultant nanoparticles were characterized by UV-vis-NIR, transmission electron microscopy (TEM), FT-IR spectroscopy, X-ray diffraction (XRD) and thermogravimetric analysis (TGA). The interaction between nanoparticles with carbonyl group of apiin compound was confirmed by using FT-IR analysis. Can drinking several cups of green tea a day keep the doctor away? This certainly seems so, given the popularity of this practice in East Asian culture and the increased interest in green tea in the Western world. Several epidemiological studies have shown beneficial effects of green tea in cancer, cardiovascular, and neurological diseases. The health benefits associated with green tea consumption have also been corroborated in animal studies of cancer chemoprevention, hypercholesterolemia, artherosclerosis, Parkinson's disease, Alzheimer's disease, and other aging- relateddisorders. Tea catechins extracted from green tea and tea extract have potential as defense against aging and neurodegenerative diseases caused by age-associated functional deterioration and neurodegeneration from an increase in free radical generation and oxidative stress such as cancer, Parkinson's disease, Alzheimer's disease, stroke, cardiovascular disease, and diabetes.